Conservation problems of mangrove ecosystem in coastal area of Rembang Regency, Central Java - AHMAD DWI SETYAWAN; KUSUMO WINARNO (Society for Indonesian Biodiversity, 2006)
The aims of the research were to find out (i) species diversity of mangrove plats, (ii) the conservation problems of mangrove ecosystem, and (iii) restoration efford of mangrove ecosystem at coastal area of Rembang Regency, Central Java. This was descriptive research that was done qualitatively, in July until December 2003, at 3 sites of mangrove habitat in Rembang Regency, namely Pecangakan, Pasar Banggi, and Lasem. The data was collected in field surveys, in-depth interview to local people and/or local government, and examination of topographic maps of Java (1963-1965) and digital satellite image of Landsat 7 TM (July-September 2001). The result indicated that northern coast of Rembang had 27 mangrove species, i.e. 12 species of major mangrove, 2 species of minor mangrove, and 13 species of associated plants. Rhizophora had been dominated mangrove ecosystem in Lasem and Pasar Bangi; while Avicennia had been dominated in Pecangakan. The most degrading factors of mangrove ecosysrems were aquaculture and salt pond, timber logging, land reclamation and soil sedimentation, and environmental pollution. Mangrove restoration by Rhizophora in coast of Pasar Bangi had been successfully, because community based management. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: conservation problems, mangrove ecosystem, Rembang Regency, Central Java Province.